Pelatihan Penyusunan Soal-Soal Asesmen Nasional Berbasis Kompetensi (ANBK) Bagi Guru-Guru SMP/MTS Muhammadiyah di Kabupaten Klaten - Rini Setyaningsih; Sutama Sutama; M. Noor Kholid; Nuqthy Faiziyah; Christina Kartika Sari; Adi Nurcahyo (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Asesmen Nasional Berbasis Kompetensi (ANBK) is a change from the Ujian Nasional Berbasis Kompetensi (UNBK) which is an assessment program carried out on the quality of schools or educational units. The purpose of this training is to provide training related to understanding and knowledge while at the same time compiling national exam questions for mathematics teachers at SMP/MTs Muhammadiyah in Klaten regarding the preparation of UNBK questions containing HOTS. The method used in this training is an interactive method between the facilitator and the teacher so that the teacher can understand and ask questions directly about the preparation of the UN questions. The training provided is able to increase the knowledge and skills of teachers in preparing exam questions directly by implementing HOTS questions.